From Words to World: Attitudinal Appraisal Analysis of China's Anhui Provincial Tourism Branding on TikTok - Shuangyan Du; Cecilia Yin Mei Cheong; Xiaoli Dong (Leksema: Jurnal Bahasa dan Sastra, 2026)
Digital media has opened new avenues for emerging destinations to shape tourist perceptions by projecting their tourism imaginaries to global audiences. However, there is a lack of study on how tourism imaginaries are constructed through attitudinal resources, especially in the context of emerging destinations. Therefore, this study examines the discursive construction of tourism imaginaries in Anhui Province, China, through its official TikTok promotions. A corpus of 203 videos was compiled, and the verbal elements were analyzed using corpus-assisted discourse and semantic analysis. Anhui’s tourism imaginaries and the attitudinal resources based on the attitude subsystem of Appraisal Theory were identified. The evaluative meanings embedded in these imaginaries were then examined through qualitative discourse analysis. The findings show that Anhui mainly uses ‘appreciation’ and ‘affect’ resources to construct positive tourism imaginaries, which include majestic natural scenery, timeless elegance, vibrant cultural festivals, exquisite cuisine, and dynamic urban life. This study suggests that the attitude system offers a useful lens for examining the verbal construction of tourism imaginaries in digital promotional contexts and demonstrates how evaluative language can be strategically used to elevate destination branding and enhance global visibility.